Nocturnal Insect Diversity in Budeng Mangrove Forest, Jembrana, Bali - Handayani, Nadia; Riawan, I Made Oka; Syah, Moh Jafron; Bernal, Edgar (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
The mangrove ecosystem in Budeng Village plays an important ecological role, yet information on nocturnal insect diversity remains limited. This study aimed to identify the species composition and analyze the diversity of nocturnal insects in the Budeng Village mangrove forest. An exploratory study was conducted using light traps. A total of 1.900 individuals representing 8 orders, 17 families, and 19 species were recorded. The diversity (0.550), species richness (2.384), and evenness (0.186) indices were low, whereas the dominance index was high (0.801) due to the predominance of Phlebotomus sp. (1.700 individuals). Overall, the nocturnal insect community showed low diversity and high species dominance. These findings provide baseline data for biodiversity monitoring and support the potential use of nocturnal insects as bioindicators of mangrove ecosystem condition.